The Specificity of Treatment of Oral Mucosal Lesions - Khamidova Guli Komilovna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oral mucosal lesions (OMLs) are diverse pathological conditions affecting the oral cavity, ranging from benign inflammatory disorders to potentially malignant lesions. Their high prevalence and complex etiology make diagnosis and management challenging in clinical settings. Specific Background: Previous studies have shown significant diagnostic delays and inconsistent management approaches, often due to limited interdisciplinary collaboration and inadequate awareness among non-specialist practitioners. Knowledge Gap: Despite the clinical importance of OMLs, there remains a lack of comprehensive synthesis addressing the specificity of treatment—how therapeutic strategies should be adapted to lesion type, etiology, and patient characteristics. Aims: This study aims to systematically review and synthesize evidence on lesion-specific treatment strategies for OMLs from 2018–2024 to identify trends in therapeutic efficacy and patient outcomes.Results: Findings reveal that etiology-based treatments—such as corticosteroids and immunomodulators for autoimmune lesions, antifungal agents for infections, and lifestyle modifications for non-inflammatory lesions—achieve higher efficacy, fewer recurrences, and improved quality of life. Novelty: The study highlights the necessity of integrating personalized, etiology-specific, and interdisciplinary approaches within oral medicine practice. Implications: The results emphasize developing standardized clinical guidelines, incorporating oral medicine into general medical education, and advancing toward precision-based, patient-centered oral healthcare.Highlight : The study focuses on the specificity of treatment according to lesion type and underlying cause. It highlights the importance of personalized and interdisciplinary approaches in oral healthcare. The research supports precision-based and patient-centered management to improve outcomes. Keywords : oral mucosal lesions, special treatment, oral medicine, personalized treatment, interdisciplinary care